THE PRACTICE OF DOWRY IN THE PERSPECTIVE OF HINDUISM IN INDIA - Vohra, Sumona (Jurnal Ilmiah Peuradeun, 2015)
Hindu religious notions have ingrained a sense of powerlessness in the psyche of many Indian women. Women are discouraged from making complaints of dowry harassment and abuse in the name of defending ?family honor?. Awareness of women?s status in India is a key element for change and abolition of dowry abuse. But, families should be encouraged to defend the rights of its women. This needs to extend outward so greater solidarity among women can be built since women are often the ones inflicting and perpetuating the abuse of young brides. All such behavior would help to alter the core attitudes that victimized women develop of themselves. In these ways, women can empower their existence within the context not only of policymaking, but also within a world that will promote equality, respect, and dignity for all living beings.